Pengaruh Lingkungan Kerja Terhadap Semangat Kerja Guru - Jakandar, Lalu Iwan Eko; Fikriah, Asfa (Jurnal Manajemen & Budaya, 2024)
A comfortable working environment is the most important thing for teachers, because a clean and comfortable working environment will increase their work morale. This work spirit is what the school really needs, so that the school's goals can be achieved. This research aims to determine the influence of the work environment on teacher morale at SMPI Baussalam, North Lombok. The type of research used in this research is quantitative research. This research was conducted on all teaching and educational staff through distributing questionnaires. To find out whether there is a significant influence of work environment variables on teacher morale at SMPI Babussalam North Lombok. The method used to obtain data in this research is the questionnaire method as the main method and documentation as the supporting method. Meanwhile, the data analysis used is statistical analysis using the product moment formula. The results of data analysis obtained in this study were 0.746, while the t table was 0.514, indicating (0.746>0.514) at a significance level of 5%. So (Ha) the alternative hypothesis is accepted and (Ho) the null hypothesis is rejected. The conclusion of this research is: There is a significant influence of the work environment on teacher morale.